Knowledge and perception about the Medical Humanities before and after a national workshop - Shankar, PR; Subish, P; Paudel, R (Journal of College of Medical Sciences-Nepal, 2012)
Medical Humanities programs are common in medical schools in developed nations. In Nepal modules have been conducted at Manipal College of Medical Sciences (MCOMS), Pokhara and KIST Medical College (KISTMC), Lalitpur. A workshop was conducted on 26th September 2010 to familiarize participants with MH. Faculty members, medical and nursing students and doctors participated. Pre and post test were administered to study knowledge and perception about MH. Differences in scores among different subgroups of participants and before and after the workshop were explored. The workshop used interactive small group learning strategies to introduce participants to different aspects of MH. Group work, group presentations, facilitator presentations, interpretation of paintings, brainstorming sessions, and role-plays were the main learning modalities used. Participants’ knowledge and perception about MH was studied by noting their agreement with a set of 25 statements using a modified Likert-type scale. Median total scores were compared among different subgroups of respondents and before and after the module. Twenty-three of the 26 participants (88.5%) completed the pre and post-test. Thirteen respondents were male and 10 female. Only three respondents (13%) had been previously exposed to MH. The median total score before the workshop was 85 (maximum possible score 125). The score was higher among male respondents. The median total score after the workshop was 98 and was significantly higher compared to that before the workshop. The workshop was effective in increasing knowledge and perception of participants about MH. A follow up workshop to consolidate the initial gains is required and is being planned. Journal of College of Medical Sciences-Nepal, 2011, Vol-7, No-2, 72-79 DOI: http://dx.doi.org/10.3126/jcmsn.v7i2.6688